PEMBELAJARAN MENULIS ESSAI MELALUI MEDIA MASSA SURAT KABAR DALAM PEMBENTUKAN BERPIKIR KRITIS (PIONIR: JURNAL PENDIDIKAN, 2021)
Writing skills are the skills with the highest level of difficulty for learners compared to the other three skills. Writing activity is a form of manifestation of language skills and abilities that are most recently mastered by language learners after listening, speaking, and reading skills. The ability to write essays is an important and strategic skill for students. Through an essay it allows students to make a positive contribution to problems that occur in society, among others, by pouring out bright ideas as outlined in essay writing. Essays can also foster a critical and creative spirit in students without causing anarchist actions as is often the case among students when conveying aspirations to other parties. At the student level, critical thinking formation can be done by writing essays. Because by writing an essay, students will be asked to give their views on a problem. When they understand a problem well and are able to analyze it, they have given an idea or idea about a problem or issue that is being discussed. The student level is the level where they have matured in thinking and are able to properly absorb various issues or problem topics that exist around them. Newspaper mass media with a diverse scope of discussion and lies in its ability to present news and ideas about the development of society in general, which can affect modern life as it is today. In addition, newspapers are able to convey something at any time to their readers through educational newspapers, information and interpretations of several things, so that most of the community depends. Based on this, the newspaper mass media can be an alternative media in writing essays.